Monic divisors with canonical diagonal form diag(1,…,1,φ(x),…,φ(x)) of polynomial matrices over infinite field (in Ukrainian) - A. M. Romaniv (Математичні Студії, 2011)
Necessary and sufficient conditions existence of monic divisors with canonical diagonal form diag(1,…,1,φ(x),…,φ(x)) of polynomial matrices over infinite field established.